The crisis of the "Empty chair" - Harst, Jan van der 1957-; Harryvan, Anjo G. 1957-; Varsori, Antonio; Schönwald, Matthias; Vai͏sse, Maurice (Crises and compromises, 2001)
Schönwald, M.: Walter Hallstein and the "Empty chair" crisis 1965/66. - S. 157-171. Harryvan, A. G.; Harst, J. v. d.: For once a united front. The Netherlands and the "Empty chair" crisis of the mid-1960s. - S. 173-191. Vai͏sse, M.: La politique européenne de la France en 1965. Pourquoi "la chaise vide"? - S. 193-214. Varsori, A.: Italy and the "Empty chair" crisis (1965-66). - S. 215-225. Oppelland, T.: "Entangling alliances with none" - neither de Gaulle nor Hallstein. The European politics of Gerhard Schröder in the 1965/66 crisis. - S. 227-243